2022
DOI: 10.1177/02683555221142531
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of polidocanol sclerotherapy in venous malformation treatment: Patient-perceived improvement and satisfaction

Abstract: Purpose This study evaluated the results of polidocanol sclerotherapy in the treatment of venous malformations (VM) including patient satisfaction, perceived improvement, and predictors of satisfaction. Material and Method Patients with VM that underwent polidocanol foam sclerotherapy between June 2013 and July 2021 in a single center were retrospectively evaluated. Patient demographics, VM, and treatment characteristics were analyzed. Patient-reported outcomes and satisfaction were analyzed with a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 39 Predictors of lesion volume change and subjective measures vary widely in previous reports, with some studies finding no predictive factors, while some factors, such as size, lesion diffusion, sex, and number of sclerotherapy sessions have been reported to impact sclerotherapy outcomes. 16 , 30 , 40 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 Predictors of lesion volume change and subjective measures vary widely in previous reports, with some studies finding no predictive factors, while some factors, such as size, lesion diffusion, sex, and number of sclerotherapy sessions have been reported to impact sclerotherapy outcomes. 16 , 30 , 40 42 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no consensus on the ideal sclerosing agent, with common agents including absolute ethanol, polidocanol foam, bleomycin, and foam sodium tetradecyl sulfate (STS). 13 16 While anhydrous ethanol has been considered the most effective sclerosing agent for reducing VMs volume, its use is associated with serious complications, such as bleeding and ulcers. 12 Recently, bleomycin polidocanol foam (BPF) has gained widespread acceptance in the treatment of VMs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous published studies have shown foam has much greater efficacy compared with liquid, with less sclerosing agent needed. [7][8][9][10][11] The concentration of polidocanol was 1%. The procedure was performed under local anesthesia.…”
Section: Methodsmentioning
confidence: 99%